KINERJA KAMBING BLIGON JANTAN YANG DIBERI PAKAN FERMENTASI COMPLETE FEED BERBASIS SUMBER PAKAN LOKAL DI KELOMPOK TERNAK PURWO MANUNGGAL - , NILA KUSUMA WARDANI; , Ir. I Gede Suparta Budisatria, M. Sc., P.hD. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was conducted to investigate the effect of fermented complete feed on feed intake, average daily gain, feed conversion, and feed cost per gain. Eight Bligon goats with 8 â 10 month old were used in this study